Early Childhood Education Training in Nunavut: Insights from the Inunnguiniq (“Making of a Human Being”) Pilot Project - Mearns, Ceporah; Healey Akearok, Gwen; Cherba, Maria; Nevin, Lauren (First Peoples Child & Family Review)

(untitled) (First Nations Child and Family Caring Society of Canada, 2020)
In the past two decades, evidence has shown that quality early childhood education (ECE) has lasting positive impacts, enhances wellbeing in many domains, and contributes to reducing economic and health inequalities. In Canada, complex colonial history has affected Indigenous peoples’ child-rearing techniques, and there is a need to support community-owned programs and revitalize traditional values and practices. While several studies have described Indigenous approaches to childrearing, there is a lack of publications outlining the core content of preschool staff training and exploring Indigenous early childhood pedagogy. This article contributes to the literature by highlighting the features of a highly effective training model rooted in Inuit values that has been implemented in Nunavut. After describing how early childhood education is organized in Nunavut, we outline the challenges related to staff training and present the development and the pilot implementation of an evidence-based training program. We then discuss its successes and challenges and formulate suggestions for professionals and policymakers to enhance early childhood educators’ training in the territory.